A virtual workbench applied to automation: student's response analysis - Machado, José (2015)
This paper presents a Virtual Workbench for Automation teaching/learning at undergraduate education level. The methodology defined as well as the formalism and the software tools adopted in the implementation are presented. A case study is detailed following the defined steps. The platform was tested by students attending the Process Control and Automation curricular unit from the 3rd year of the Master in Engineering and Industrial Management of University of Minho. A questionnaire was design to gauge the undergraduate student's acceptance and the platform' effectiveness. The research found that the Virtual Workbench allows new strategies and teaching methodologies related with laboratorial practice providing illustrative real-world examples.